2006
DOI: 10.3177/jnsv.52.421
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nerve Growth Factor by Zinc Supplementation with Concurrent Vitamin A Deficiency Does Not Improve Memory Performance in Mice

Abstract: SummaryWe investigated the effects of dietary supplementation of zinc (Zn) with or without vitamin A (Vit. A), to elucidate any cross activity between the two micronutrients, on memory and nerve growth factor (NGF) production in ddY male mice depleted for the two elements. After 3 mo-feeding with a Zn and Vit. A deficient (VAD) diet, mice were divided into three groups and replenished with normal Zn with VAD diet (NZ-VAD), high Zn with VAD diet (HZ-VAD) or normal Zn ϩ normal Vit. A (NZ-NVA) for additional 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…For example, zinc supplementation given chronically to vitamin A-deficient mice improved nerve growth factor levels in the hippocampus, cerebral cortex and cerebellum extracts, however did not enhance mouse memory outcomes when vitamin A was deprived [35]. Zinc deficiency during lactation in rats was found to have lasting growth deficits after dietary rehabilitation and delay the first-week post-natal reflexes, including auditory startle, air righting and rope descent as compared to nourished controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, zinc supplementation given chronically to vitamin A-deficient mice improved nerve growth factor levels in the hippocampus, cerebral cortex and cerebellum extracts, however did not enhance mouse memory outcomes when vitamin A was deprived [35]. Zinc deficiency during lactation in rats was found to have lasting growth deficits after dietary rehabilitation and delay the first-week post-natal reflexes, including auditory startle, air righting and rope descent as compared to nourished controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should also be noted that receiving multivitamins could alter neuropsychological performance. In an animal study it was shown that dietary supplementation of zinc may increase nerve growth factor; however, memory was improved only when vitamin A was sufficient (28).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of BDNF and NGF have been shown to decrease in zinc(II) deficient mice [125], hence zinc(II) dietary supplementation seems to replenish the NGF [126], as well as the BDNF, level [127]. Moreover, chronic treatments with zinc(II) ion induced a BDNF mRNA upregulation in the cortex and hippocampus [128], strongly suggesting a more direct role of this metal ion in the neurotrophins expression.…”
Section: Metals and Neurotrophinsmentioning
confidence: 99%